2016
DOI: 10.1176/appi.ps.201500305
|View full text |Cite
|
Sign up to set email alerts
|

Expedited Medicaid Enrollment, Mental Health Service Use, and Criminal Recidivism Among Released Prisoners With Severe Mental Illness

Abstract: Objective To investigate whether Washington State’s 2006 policy of expediting Medicaid enrollment for offenders with severe mental illness released from state prisons increased Medicaid access and use of community mental health services while decreasing criminal recidivism. Methods A quasi-experimental design with linked administrative data was used to select all prisoners with a severe mental illness (schizophrenia or bipolar disorder) released during the policy’s first two years (January 1, 2006 through De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…In Wenzlow et al (2011), the study’s secondary outcomes were significant with more of the intervention group having contact with mental health services ( p  = .009) and being prescribed medication ( p  = .041) in the 90 days following release. Morrissey et al (2016) also found participants in the intervention group also had higher rates of mental health and other health service use as well as prescribed medication and although this information was recorded from insurance based payment systems the differences appear robust.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In Wenzlow et al (2011), the study’s secondary outcomes were significant with more of the intervention group having contact with mental health services ( p  = .009) and being prescribed medication ( p  = .041) in the 90 days following release. Morrissey et al (2016) also found participants in the intervention group also had higher rates of mental health and other health service use as well as prescribed medication and although this information was recorded from insurance based payment systems the differences appear robust.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the included studies were conducted in the United States of America (US; n = 10; Brown et al 2013; Buck et al 2011; Burke and Keaton 2004; Hartwell and Orr 1999; Kesten et al 2012; Morrissey et al 2016; Roskes and Feldman 1999; Solomon and Draine 1995; Theurer and Lovell 2008; Trupin et al 2011; Wenzlow et al 2011) with two studies conducted in England (Jarrett et al 2012; Shaw et al 2017) and one in Australia (Green et al 2016). Nine used a wide geographical area which included urban and rural settings, whereas four related to a single urban area (Brown et al 2013; Buck et al 2011; Roskes and Feldman 1999; Solomon and Draine 1995; Theurer and Lovell 2008).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations